2006
DOI: 10.1007/s00359-006-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Temperature acclimation alters cardiac performance in the lobster Homarus americanus

Abstract: The American lobster is a poikilotherm that inhabits a marine environment where temperature varies over a 25 degrees C range and depends on the winds, the tides and the seasons. To determine how cardiac performance depends on the water temperature to which the lobsters are acclimated we measured lobster heart rates in vivo. The upper limit for cardiac function in lobsters acclimated to 20 degrees C is approximately 29 degrees C, 5 degrees C warmer than that measured in lobsters acclimated to 4 degrees C. Warm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
3
28
0
1
Order By: Relevance
“…1C). A similar effect of acclimation on lowtemperature heart rate has been reported in lobsters (Camacho et al, 2006), mussels of the genus Mytilus (Braby and Somero, 2006) and snails of the genus Chlorostoma (formerly the genus Tegula) (Stenseng et al, 2005). Studies in fishes also have shown that lowtemperature acclimation results in a broad suite of cardiac changes including enhanced ability to sustain function at low temperatures (Jayasundara and Somero, 2013), increased heart mass (Vornanen et al, 2005), and up-regulation of genes involved in protein synthesis and transcriptional regulation (Gracey et al, 2004).…”
Section: Acclimatory Plasticitysupporting
confidence: 81%
See 2 more Smart Citations
“…1C). A similar effect of acclimation on lowtemperature heart rate has been reported in lobsters (Camacho et al, 2006), mussels of the genus Mytilus (Braby and Somero, 2006) and snails of the genus Chlorostoma (formerly the genus Tegula) (Stenseng et al, 2005). Studies in fishes also have shown that lowtemperature acclimation results in a broad suite of cardiac changes including enhanced ability to sustain function at low temperatures (Jayasundara and Somero, 2013), increased heart mass (Vornanen et al, 2005), and up-regulation of genes involved in protein synthesis and transcriptional regulation (Gracey et al, 2004).…”
Section: Acclimatory Plasticitysupporting
confidence: 81%
“…This is slightly less than the maximum acclimation ability in cardiac thermal tolerance seen for the low intertidal porcelain crabs P. eriomerus and P. manimaculis (2.1 and 3.5°C, respectively), which had the highest acclimation ability of six congeneric species studied (Stillman, 2004). Lobsters were also quite plastic, with a 3°C increase in heat tolerance between 4 and 20°C acclimation (Camacho et al, 2006). While C. maenas was less plastic than these species, it maintains a considerably higher constitutive heat tolerance (Fig.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…In decapod crustaceans many studies have used the changes in a vegetative index to monitor the effects of a wide range of environmental variables on the physiology: water currents (Larimer, 1964), P O2 (Airriess and McMahon, 1994), ammonia (NH 3 ) (Bloxham et al, 1999), heavy metals (Aagaard et al, 2000), ambient CO 2 /O 2 (Gannon and Henry, 2004), water temperature (Camacho et al, 2006). In addition, the responses to several types of stimuli (tactile and chemical cues) were examined for their effects on the heart and ventilatory rate of crayfish, finding a reflex inhibition in the majority of them (Larimer, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…Such manipulations make it difficult to compare the actions of different substances on CG motor output. For example, recent studies using the isolated heart preparation have shown that cardiac performance in the lobster, Homarus americanus, is temperature-dependent (Camacho et al, 2006;Worden et al, 2006). Secondly, studies on the isolated CG have been done using many different species, which poses the question of whether the effect of a single modulator in one Neuromodulators can change the output of neural circuits.…”
Section: Introductionmentioning
confidence: 99%